Relationship Between Knowledge, Attitude and Behavior of Mothers Towards Infant and Child Feeding (PMBA) 6-59 Month - Akulin Yogi; Nur Al-Faida; Alfred Denius Lambey (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background:PMBA is one of the government programs to reduce child mortality rates and improve the quality of life of mothers in accordance with improvements in maternal behavior in PMBA. PMBA includes IMD, Exclusive Breastfeeding, MP-ASI, Breastfeeding up to 2 years of age. Objective: To find out about the Relationship between Knowledge Level, Attitude and Mother's Behavior towards PMBA 6-59 Monthsin the Working Area of ​​the Yabomaida Health Center, Paniai Regency. Method: This research method is correlational analytic with a cross-sectional approach. The research population consisted of 190 infants and children.withThe research sample consisted of 66 people who had a Relationship between the Level of Knowledge, Attitude and Behavior of Mothers towards PMBA 6-59 Months.in the Working Area of ​​the Yabomaida Health Center, Paniai Regency.The sampling technique used purposive sampling. Data analysis used the Statistical program for social science (SPSS) version 16.0 computer application program and used the chi-square test. Results: the results of the relationship between the level of maternal knowledge of PMBA based on the p value = 0.04 (<0.05), while the mother's attitude towards PMBA based on the p value = 0.03 (<0.05), and the mother's behavior towards PMBA based on the p value = 0.02 (<0.05). Conclusion: There is an influence of PMBA on knowledge and attitudes and PMBA practices in the Yabomaida Health Center work area, Paniai Regency, which obtained the p value <0.05. Suggestion: the need for PMBA 6-59 months in the posyandu counseling andIn the Working Area of ​​the Yabomaida Health Center, Paniai Regency.